2002
DOI: 10.1207/s15328023top2902_04
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating End-of-Life Issues into Psychology Courses

Abstract: The American Psychological Association's Working Group on Assisted Suicide and End-of-Life Decisions (2000) recently called for the development of resources to assist training programs in incorporating end-of-life issues into undergraduate and graduate courses. After explaining why teaching about the dying process is relevant to psychology, I provide suggestions for how instructors can include end-of-life issues and decisions in courses on ethical, legal, and professional issues; adult and life span developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Similar to this finding, our qualitative data revealed that the Indian students felt more competent to work in a palliative care setting and that the course had raised their awareness and decreased their worries about the concept of death [35,36]. This result highlights the importance of death education in the training of future professionals, such as psychology students, in the field of personal care [37,38].…”
Section: Discussionsupporting
confidence: 80%
“…Similar to this finding, our qualitative data revealed that the Indian students felt more competent to work in a palliative care setting and that the course had raised their awareness and decreased their worries about the concept of death [35,36]. This result highlights the importance of death education in the training of future professionals, such as psychology students, in the field of personal care [37,38].…”
Section: Discussionsupporting
confidence: 80%
“…Second, grief and loss issues can have an effect on counselors, either as a result of working with the clients' issues or because they connect to the counselors' own life issues, attitudes, and experiences (Hunt & Rosenthal, 2000;Rando, 1984;Werth, 2002). In some cases, the extent of the client's issues can lead to empathy fatigue, which can impair the counselor's ability to serve clients effectively (Stebnicki, 2000).…”
Section: Need For Grief and Loss Counseling Trainingmentioning
confidence: 99%